Nilotinib effect on hepatic and renal functions in a sample of Iraqi patients with chronic myeloid leukemia - Khaleel, Khaleed J. (Iraqi Journal of Cancer and Medical Genetics, 2017)
Background: Chronic myelogenous leukemia is a clonal disorder of the pleuripotent stem cells which accounts for about 15% of leukemias. Tyrosine kinase inhibitors (TKIs) are the first line therapy for CML which have substantially improved the prognosis of CML. Nilotinib is a second generation TKI which is being used widely. as a frontline drug for CML treatment and also for imatinib resistant cases. Nilotinib has been reported to induce hepatotoxicity and to affect renal function Objectives: The current study aims to evaluate the effect of nilotinib on liver and renal function in a sample of Iraqi patients with chronic myeloid leukaemia (chronic phase) treated with Nilotinib and its possible association with grades of other haematological parameters. Patients and Methods: Thirty three patients with chronic myeloid leukaemia and the same number of healthy controls were enrolled in this cross sectional study. All the patients were on Nilotinib hydrochloride for at least 6 months. Switching to Nilotinib treatment was due to intolerance or resistance to Imatinib. ALT, AST, blood urea, creatinine as well as other haematological parameters were measured. Results: only one patient out of thirty three( 3%) had a very high ALT and AST with grade 3 and only 2 patients (6%) were classified as grade 1 for ALT level. All the patients were within the normal range values of blood urea, creatinine and eGFR . Conclusion: Hepatotoxicity is a serious adverse effect of nilotinib that mandates regular check-up of liver function.